Lesson hub

## Can't find the answer? Try online tutoring

We have the UK’s best selection of online tutors, when and for how long you need them.

Getting 1-on-1 support is cheaper than you might think.

### Participating users

Welcome to our free-to-use Q&A hub, where students post questions and get help from other students and tutors.

You can ask your own question or look at similar Mathematics questions.

Let's solve your equation step-by-step.3x(x+4)+3(x+4)=0Step 1: Simplify both sides of the equation3x2+15x+12=0Step 2: Factor left side of equation.3(x+1)(x+4)=0Step 3: Set factors equal to 0.x+1=0 or x+4=0ans:x=−1 or x=−4

3x(x+4)+3(x+4)=0

(3x+3)(x+4)=0

3(x+1)(x+4)=0

x+1=0 and x+4=0

x=-1 or  x=-4

3x(x+4) = 3x^2 +12x

3(x+4) = 3x + 12

So: 3x(x+4) + 3(x+4) = 3x^2 +12x + 3x + 12  ----> just expanded the brackets

Therefore: 3x^2 +12x + 3x + 12  = 0

Simplify it to: 3x^2 + 15x + 12 = 0

Factorise to get: (3x + 3) (x+4) = 0

Therefore: (3x + 3) = 0 or (x+4) = 0

If: 3x + 3 = 0 --> 3x = -3 so x= -3/3 = -1

If: x+4 = 0 ---> x = -4

x = -1 or -4

Hope that helped!

Firstly take the bracket of (x+4), if x+4=0 then x must be equal to -4.

The other numbers make another bracket of (3x+3). If 3x+3=0, then 3x=-3 and so x is equal to -1

3( x+4)(x+1)=0

X= -4,  -1

3( x+4)(x+1)=0

X= -4,  -1

Browndaisha !

simply remember in math there is rule of DMAS.  it says 1. Division,Multlipication,3.Addition and 4.Subtraction. in any equation follow these steps.
you will get result.

given the equation, we can say that we have (x+4) in common.
So, we take that out, (x+4), we will have another bracket, (3x+3).

We can say that (x+4)(3x+3)=0

now we can equate, we can say either (x+4)=0 or (3x+3)=0                                                                                                x=0 -4  or 3x=0-3                                                                                                  x= -4 or x=-3/3                                                                                                      x=-4   or x=-1

expand the brackets

3x^2 + 12x + 3x + 12 = 0

Gather like terms

3x^2 + 15x + 12=0

simplify by dividing the whole equation by 3

x^2 + 5x + 4 = 0

Factorise (two numbers that added give you 5 and multiplied give you 4)

(x+1)(x+4) = 0

Thus, the two solutions are x=-1 and x=-4

If you need further help, feel free to contact me for tuition services

First, expand the brackets

So 3x^2+12x + 3x+12 =0

Then simplify it all out - ax^2+bx+c=0 is the format you want the question in to solve

3x^2 + 15x +12 =0

This is the same as 3(x^2+5x+4)=0

Now you need to find 2 numbers to multiply to make 4 (c in the equation) that also add to make 5 - 1 and 4.

Therefore x=-1 and x=-4

Check it in the equation and see if it equals 0, if it does it's right